Physiological and Molecular Characterization of an Oxidative Stress-Resistant Saccharomyces cerevisiae Strain Obtained by Evolutionary Engineering - Kocaefe-Özşen, Nazlı; Yilmaz, Bahtiyar; Alkım, Ceren; Arslan, Mevlüt; Topaloğlu, Alican; Kısakesen, Halil l̇brahim; Gülsev, Erdinç; Çakar, Z. Petek (Frontiers in Microbiology, 2022)
Oxidative stress is a major stress type observed in yeast bioprocesses, resulting in a decrease in yeast growth, viability and productivity. Thus, robust yeast strains with increased resistance to oxidative stress are in highly demand by the industry. In addition, oxidative stress is also associated with aging and age-related complex conditions such as cancer and neurodegenerative diseases. Saccharomyces cerevisiae, as a model eukaryote, has been used to study these complex eukaryotic processes. However, the molecular mechanisms underlying oxidative stress responses and resistance are unclear. In this study, we have employed evolutionary engineering (also known as adaptive laboratory evolution – ALE) strategies to obtain an oxidative stress-resistant and genetically stable S. cerevisiae strain. Comparative physiological, transcriptomic and genomic analyses of the evolved strain were then performed with respect to the reference strain. The results show that the oxidative stress-resistant evolved strain was also cross-resistant against other types of stressors, including heat, freeze-thaw, ethanol, cobalt, iron and salt. It was also found to have higher levels of trehalose and glycogen production. Further, comparative transcriptomic analysis showed an upregulation of many genes associated with the stress response, transport, carbohydrate, lipid and cofactor metabolic processes, protein phosphorylation, cell wall organization, and biogenesis. Genes that were downregulated included those related to ribosome and RNA processing, nuclear transport, tRNA, and cell cycle. Whole genome re-sequencing analysis of the evolved strain identified mutations in genes related to the stress response, cell wall organization, carbohydrate metabolism/transport, which are in line with the physiological and transcriptomic results, and may give insight towards the complex molecular mechanisms of oxidative stress resistance.